FATORES VINCULADOS À QUALIDADE DE VIDA DE CRIANÇAS E ADOLESCENTES SUBMETIDOS À TERAPIA RENAL SUBSTITUTIVA (REMUNOM, 2024)
AbstractIntroduction: Renal Replacement Therapy (RRT) is a resource used for patients with renal function failure, as it will act in a similar way to the kidneys, exerting functions in the control of electrolytes. Objective: To identify, based on existing literature, which are the main factors that contribute to the quality of life of children and adolescents undergoing Renal Replacement Therapy. Methodology: This is an integrative bibliographic review study carried out in the electronic databases National Library of Medicine National Institutes of Health (MEDLINE/PubMed), Electronic Scientific Library (SciELO) and Virtual Health Library (VHL), in which Complete and original studies were used, with a time frame from 2020 to 2024, in Portuguese, English and Spanish. Results: At the end of the research, eight articles were found that highlight that both patients and their families face limitations and restrictions resulting from treatment, profoundly affecting their lives and mental health, also demonstrating that patients on peritoneal dialysis (PD) tend to have a better quality of life than those on hemodialysis. Conclusion: Several factors were identified as influencing quality of life (QoL), including advanced age at the start of dialysis, early diagnosis of chronic kidney disease (CKD) and time since diagnosis greater than 60 months. Keywords: Kidney dialysis; Child; Adolescent; Quality of life.